2011
DOI: 10.1071/py11057
|View full text |Cite
|
Sign up to set email alerts
|

Beyond the rhetoric: how can non-government organisations contribute to reducing health disparities for Aboriginal and Torres Strait Islander people?

Abstract: The prevailing disparities in Aboriginal health in Australia are a sobering reminder of failed health reforms, compounded by inadequate attention to the social determinants shaping health and well-being. Discourse around health reform often focuses on the role of government, health professionals and health institutions. However, not-for-profit health organisations are also playing an increasing role in health policy, research and program delivery across the prevention to treatment spectrum. This paper describe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…In addition, it engenders self-pride in the Aboriginal employee and a belief that the organisation trusts and understands them ‘…believe in me and I will believe in myself’. The Heart Foundation in Western Australia (WA) found that both trust and flexibility are essential ingredients in supporting the personal development of an Aboriginal employee in a mainstream workplace [39].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, it engenders self-pride in the Aboriginal employee and a belief that the organisation trusts and understands them ‘…believe in me and I will believe in myself’. The Heart Foundation in Western Australia (WA) found that both trust and flexibility are essential ingredients in supporting the personal development of an Aboriginal employee in a mainstream workplace [39].…”
Section: Discussionmentioning
confidence: 99%
“…Aboriginal health workers employed in a mainstream health service experience little separation from their community and their workplace duty to continuously advocate and create cultural safety, ultimately increasing the risk of emotional exhaustion and burnout [41, 42]. Culturally strong and flexible workplaces enable early identification of burnout and the need for additional unexpected support such as time off for ‘sorry business’ [39, 41, 42]. In Australia, compassionate leave entitles any full- or part-time employee to 2 days paid leave [43].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This takes time [18]. Overall, there is an increased consciousness within Cancer Councils of the need for specific strategies to address the disparity seen in Indigenous cancer outcomes, although the strategic [comprehensive] approach recently described by the Heart Foundation in WA is not evident [24]. Wood and colleagues described the recognition by the National Heart Foundation at a whole-of-organizational level of the need to embrace cultural security – through proactive appointment of Indigenous people, appointment of Aboriginal people to Boards, senior committees and working groups; establishment of a dedicated Indigenous health program and team; and integration of Indigenous health across the whole organisation.…”
Section: Discussionmentioning
confidence: 99%
“…Wood et al (2011) provide the only paper in this edition focussed on Aboriginal communities. They describe the process of organisational change in a non-government organisation (NGO) as it embeds a focus on Aboriginal health within its work.…”
mentioning
confidence: 99%